Arterial Injury during Percutaneous Nephrostomy: Angiography Findings from an Isolated Porcine Kidney Model - Yang, Houmeng; Weng, Guobin; Yao, Xuping; Tang, Chunbo; Shan, Yuxi (Urology Journal, 2015)
Purpose: To investigate the extent of renal arterial injury incurred by different size of nephrostomy tracts from 10 French (F) to 32F in vitro porcine kidney. Materials and Methods: To simulate the technique of percutaneous nephrostomy we set up 12 groups of different size nephrostomy tracts from 10F to 32F, including 40 nephrostomy tracts in each group. Digital subtraction angiography (DSA) was used to inspect and analysis of arterial injury. Results: When the size of nephrostomy tracts is increased from 10F to 32F, the degree of arterial injury is also aggravated. With 14F compared to 24F, the number of nephrostomy tracts with serious arterial injury was 12 (12/40) and 23 (23/40), respectively (P < .05). With 18F compared to 30F, the number of nephrostomy tracts with serious arterial injury was 16 (16/40) and 30 (28/40), respectively (P < .01). Conclusion: When the size of nephrostomy tract is increased, the degree of renal arterial injury is also heightened. When 18F tracts was compared to 30F tracts and 14F tracts compared to 24F tracts, obvious reduction of arterial injury is observed.